2016
DOI: 10.1111/cogs.12354
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Moral Beliefs, Memories, and Preferences in Representations of Identity

Abstract: People perceive that if their memories and moral beliefs changed, they would change. We investigated why individuals respond this way. In Study 1, participants judged that identity would change more after changes to memories and widely shared moral beliefs (e.g., about murder) versus preferences and controversial moral beliefs (e.g., about abortion). The extent to which participants judged that changes would affect their relationships predicted identity change (Study 2) and mediated the relationship between ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 62 publications
(78 reference statements)
3
62
0
Order By: Relevance
“…Additionally, the religious teachings of Christianity (the dominant religious group in the United States and the affiliation of most religious participants in the current study) do not explicitly describe God's beliefs about these behaviours. Finally, these items have been used in prior work distinguishing controversial versus widely shared moral beliefs (Heiphetz, Strohminger, et al ., ; Heiphetz & Young, ). Second, after reporting whether an agent held a particular belief, participants answered ‘yes’, ‘maybe’, or ‘no’ to the following question: ‘Will [agent] always think that?’ Third, to ensure that children understood the word ‘always’, the experimenter asked four questions at the end of the session (e.g., ‘Will your mom always be older than you?’; see Appendix).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the religious teachings of Christianity (the dominant religious group in the United States and the affiliation of most religious participants in the current study) do not explicitly describe God's beliefs about these behaviours. Finally, these items have been used in prior work distinguishing controversial versus widely shared moral beliefs (Heiphetz, Strohminger, et al ., ; Heiphetz & Young, ). Second, after reporting whether an agent held a particular belief, participants answered ‘yes’, ‘maybe’, or ‘no’ to the following question: ‘Will [agent] always think that?’ Third, to ensure that children understood the word ‘always’, the experimenter asked four questions at the end of the session (e.g., ‘Will your mom always be older than you?’; see Appendix).…”
Section: Methodsmentioning
confidence: 99%
“…Second, we included beliefs about controversial as well as good and bad behaviours. Controversial behaviours, such as telling prosocial lies, elicit disagreement about whether they are right or wrong (Heiphetz, Strohminger, & Young, ; Heiphetz & Young, ). Few religious teachings address God's views regarding such behaviours, allowing us to discover how individuals conceptualize God's beliefs in cases where the ‘theologically correct’ answer is not clear.…”
Section: Studymentioning
confidence: 99%
“…For example, Gino and Desai (2012) showed that asking participants to recall childhood memories triggered the concept of “moral purity” (“Children are innocent and virtuous.”); which in turn affected their prosocial behavior. This suggests that our sense of the self may be influenced and momentarily re-structured by moral involvements (Bergman, 2002; Hardy and Carlo, 2005; Heiphetz et al, 2016), indicating a moral self-regulating mechanism (Escobedo and Adolphs, 2010); an essential moral self, suggesting that “Moral traits are considered more important to personal identity than any other part of the mind” (Strohminger and Nichols, 2014, p. 168).…”
Section: Introductionmentioning
confidence: 99%
“…These same traits and characteristics, openly displayed and acted upon, also define who we are in the eyes of others (Heiphetz, Strohminger, and Young 2016;Strohminger and Nichols 2014). The concept of identity describes both the first person sense of self, and the way one is seen by others.…”
Section: IVmentioning
confidence: 97%
“…The set of values we endorse and the moral character we possess are important to making us who we are as a person. If we change our central value commitments, or change from being a kind person to a cruel person, then we are inclined to say that we have become someone different (Heiphetz, Strohminger, and Young 2016).…”
Section: IVmentioning
confidence: 99%